Amphotericin B and Fluconazole, a Potent Combination Therapy for Cryptococcal Meningitis - Larsen, Robert A. (American Society for Microbiology, 2004)
We evaluated the antifungal activities of amphotericin B, fluconazole, and flucytosine, alone and in combination, in a murine model of cryptococcal meningitis. The objectives were to determine the greatest antifungal effects achievable with these drugs alone or in combination. Meningitis was established in male BALB/c mice weighing 23 to 25 g by intracerebral injection of Cryptococcus neoformans. Treatment was started on day 2. Amphotericin B was tested at 0.3 to 1.3 mg/kg of body weight/day by slow intravenous injection. Fluconazole at 10 to 40 mg/kg/day and flucytosine at 20 to 105 mg/kg/day were administered in the sole source of drinking water. The mice were killed at 16 days, and the numbers of fungal colonies in the brain were quantified. The association between the response and the dose combination was evaluated by local nonparametric response surface methods; 99% confidence intervals were used to evaluate the antifungal effects. Ninety-five percent of the mice treated with amphotericin B at 0.5 mg/kg survived to the end of the experiment, regardless of the fluconazole or flucytosine dose used. The greatest activity was seen with amphotericin B plus fluconazole with or without flucytosine. However, the addition of flucytosine did not increase the antifungal activity. Given the widespread availability of amphotericin B and fluconazole and the relative safety profile of fluconazole compared to that of flucytosine, the full potential of this two-drug combination deserves further evaluation.